Arabic Language and Keeping pace with Developments: between Authenticity and Evolution - Fatimah Salih Aemarah Almadani (Journal of Scientific and Human Dimensions, 2025)
The Arabic language is characterized by a deeply rooted structure and a robust system that has historically combined the authenticity of its origins with a remarkable capacity for evolution. This research highlights this delicate balance by studying the linguistic features of Arabic that have endowed it with consistency and stability, followed by an exposition of its mechanisms for linguistic expansion, such as derivation (Ishtiqaq) and arabization (Ta'reeb), which grant it the flexibility to accommodate scientific and technological developments. The study concludes that Arabic is not a static language but a dynamic system capable of interacting with the current era and meeting the demands of expression and communication without abandoning its fundamental identity. While the language faces contemporary challenges, notably the dominance of foreign languages and the scarcity of Arabic digital content, its intrinsic structural capabilities and semantic richness confirm its enduring ability to remain current. Enhancing this balance requires conscious educational and institutional efforts.
Keywords: Arabic Language; Authenticity; Derivation; Arabization; Linguistic Expansion